Efeito da hidrólise ácida em propriedades de nanocelulose vegetal - Farias, Daniel Tavares de (2022)
Cellulose nanofibrils (CNF) and cellulose nanocrystals (CNC) are two types of nanocellulose that have morphological, structural and surface characteristics that allow them to be applied in the industrial and biomedical sectors for the development of green products with high added value and low environmental impact, and can be extracted from abundant and renewable resources such as agro-industrial waste and forestry resources. CNCs are extracted from plant cellulose, usually by mechanical or chemical methods or a combination of these to obtain CNCs with a diameter of less than 100 nm and a length of several micrometers. CNCs are isolated from the acid hydrolysis of cellulose fibers using concentrated mineral acid. Sulphuric acid is the most commonly used acid hydrolysis acid because it preferentially breaks the cellulose chains from the amorphous regions of the cellulose chains, releasing CNCs with high crystallinity and colloidal stability in aqueous media. The general aim of this study was to obtain nanocellulose from vegetable cellulose sources and to check the effect of hydrolysis parameters on the yield and properties of nanocellulose. In Article 1, delignified kraft pulp from Acacia mearsii wood was hydrolyzed with different concentrations of sulfuric acid in order to verify the effect of acid concentration on the yield and properties of cellulose nanocrystals. Article 2 aimed to individualize cellulose nanofibrils from açaí waste by applying acid hydrolysis using sulphuric acid with different hydrolysis times as a pre-treatment for nanofibrillation in an ultrasonic probe processor. The results obtained in this study showed that it is possible to obtain high yields and nanocellulose with high crystallinity, stability in aqueous media, and high thermal stability by using the acid hydrolysis method to obtain CNC from the delignified kraft cellulosic pulp of Acacia mearnsii in Article 1. And applying acid hydrolysis as a pre-treatment for ultrasonic nanofibrillation to obtain cellulose nanofibrils from delignified açaí residue in Article 2. In both articles, it was found that varying the hydrolysis parameters was responsible for changes in the yield and morphological, thermal and structural properties of the nanocellulose.